Cyber-Conflict, Cyber-Crime, and Cyber-Espionage - Weissbrodt, David (2013)
Computers and the Internet have changed and are continuing to change the way governments, militaries, businesses, and other organs of society manage their activities. While computers can improve efficiency, they are vulnerable to cyber-attack, cyber-crime, and cyber-espionage. 1 The international community, states, and businesses are still adapting to the unique set of challenges posed by cyber-attack, cyber-crime, and cyber-espionage. States are creating military operations that specialize in cyber-attack and defense to adapt to these relatively new threats to national security operations.